Heterogeneity in Silk Piezoelectricity - Gunay, Seckin D. (WILEY-V C H VERLAG GMBH, 2025)
Experimental studies demonstrates that silk exhibits good piezoelectric properties among biological materials. It has been proven by experimenters that the material, which contains amorphous and secondary structures, acquires this property from beta-sheet crystals. In this study, the piezoelectric properties of silk II beta-sheets are investigated at the microscopic level. Models existing in the literature are examined using computational methods. Shear deformation is applied to these structures, and piezoelectric coefficients (d14)$( {{{d}_{14}}} )$ are calculated. Two models provided by recent studies, Asakura A and B, form silk fibroin and are distributed with a 2:1 ratio. The overall piezoelectric property emerges with the contribution of both. It is determined that there is a six-fold difference between the piezoelectric coefficients of the two models. This signifies that these beta-sheet crystal structure models that made up the silk has very different piezoelectric properties. Thus, the heterogeneity in the structure also exists in the piezoelectric property. Theoretically, there is a possibility to increase the silk piezoelectricity by increasing the Asakura Model A beta-sheet concentration.
Keywords: dipole moment; beta-sheet; piezoelectric coefficient; silk; FIBROIN; DYNAMICS; GROMACS; Science & Technology - Other Topics